2021
DOI: 10.1029/2021wr030916
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Soil Desiccation Cracking Using an Infrared Thermal Imaging Technique

Abstract: Soil desiccation cracking is a ubiquitous natural phenomenon and becomes more intensive under climate extremes such as drought, imposing significant concerns in various fields, such as geology, environment, agriculture and engineering (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 116 publications
(216 reference statements)
0
7
0
Order By: Relevance
“…Lower moisture content results in a higher conversion of solar radiation into sensible heat (measurable as temperature) ( Figure 1 ), in opposite to high soil moisture conditions, in which the incident solar energy is used to evaporate water ( Heilman et al., 1994 ). Soil water evaporation reduces ST, and the temperature difference between soil and the atmosphere is proportional to the evaporation rate ( Zeng et al., 2021 ) and as a consequence soil surface temperature inversely correlates with soil water content ( Krapez et al., 2012 ). As a result, the typical wet-dry irrigation cycles occurring in irrigated crops often result in spikes in ST (See Figure 3 ).…”
Section: Determinants Of Soil Temperature In Vineyardsmentioning
confidence: 99%
“…Lower moisture content results in a higher conversion of solar radiation into sensible heat (measurable as temperature) ( Figure 1 ), in opposite to high soil moisture conditions, in which the incident solar energy is used to evaporate water ( Heilman et al., 1994 ). Soil water evaporation reduces ST, and the temperature difference between soil and the atmosphere is proportional to the evaporation rate ( Zeng et al., 2021 ) and as a consequence soil surface temperature inversely correlates with soil water content ( Krapez et al., 2012 ). As a result, the typical wet-dry irrigation cycles occurring in irrigated crops often result in spikes in ST (See Figure 3 ).…”
Section: Determinants Of Soil Temperature In Vineyardsmentioning
confidence: 99%
“…Capturing the soil temperature change caused by evaporation can greatly help to a better understanding of soil cracking behaviors, since soil cracking is majorly caused by evaporation. Recently for first time, Zeng and co‐workers [ 224 ] emphasize the possible environmental use of the IR thermal imaging sensor approach to look into the fundamental parameters governing interplay between atmosphere and soil, and anticipate soil dehydration cracks (Figure 20b), and found that the soil‐atmosphere temperature differentials affects evaporation and soil desiccation cracking.…”
Section: Applicationsmentioning
confidence: 99%
“…b) Soil desiccation cracking schematic view, temporal evolution and correlation between temperature difference and evaporation rate Reproduced with permission. [ 224 ] Copyright 2023, Wiley‐VCH. c) Thermal infrared based winter‐time monitoring of surface hydrology (A), Stream network size and surface saturation (B), summer time airborne mosaic of headwater (C), stream network and spl split stream network expansion/connectivity through pixels (D).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the soil gets dry over the experimental dates, the evaporation rate is calculated using Eq. ( 7), which is adapted from reference [17]:…”
Section: Soil Water Evaporationmentioning
confidence: 99%